2018
DOI: 10.1016/j.imr.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

In vitro anticancer activities of Withania coagulans against HeLa, MCF-7, RD, RG2, and INS-1 cancer cells and phytochemical analysis

Abstract: BackgroundThe Pakistani Salt Range has a rich floral diversity including Withania coagulans from the Solanaceae family.MethodsThe crude methanolic extracts of the root, leaf, leaf stalk, and fruit of this plant were screened for their cytotoxic activity against human (HeLa, MCF-7, RD) and rat (RG2 and INS-1) cancer cell lines at 20 μg/mL and compared to methotrexate. The IC50 values indicated that leaf stalk and fruit extracts exert an 80% or higher cytotoxic activity against all cell lines at 24 hours.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…A large number of plant metabolites are utilized against various diseases, including cancer [2,3]. The herbal medicines have played an important role in the prevention and treatment of cancer, which execute their multiple therapeutic effects by inhibiting cancer activating enzymes and hormones, promoting the production of protective enzymes, inducing antioxidant action and enhancing immunity, stimulating DNA repair mechanism, thus showing an anticancer effect.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of plant metabolites are utilized against various diseases, including cancer [2,3]. The herbal medicines have played an important role in the prevention and treatment of cancer, which execute their multiple therapeutic effects by inhibiting cancer activating enzymes and hormones, promoting the production of protective enzymes, inducing antioxidant action and enhancing immunity, stimulating DNA repair mechanism, thus showing an anticancer effect.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer therapy of plant origin is at the forefront due to naturally inherent compounds that are readily available, less toxic, and cost-effective. Compounds, including saponins, phenols, and glycosides have reportedly been used in chemotherapy [ 31 ]. Qualitative phytochemical screening of this study ( Table 4 ) confirmed the presence of these compounds in C. rubens and is similar to the findings of Ojo and Adenegan-Alakinde [ 18 ], except the absence of tannins, which may be due to extraction solvent (alcohol) they used.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few years, medicinal plant-based therapeutics have gained great attention in the treatment of cancer as they are more cost effective, natural, readily available and exhibit fewer undesirable side effects. In addition, the potential of plant-derived compounds to induce cellular apoptosis constitute a key event in anticancer activities of medicinal plants (Desai et al, 2008[ 8 ]; Maqsood et al, 2018[ 20 ]; Ahmed et al, 2019[ 2 ]). Herein, we performed a pilot study to firstly examine the cytotoxic and apoptotic effects of various extracts of S. amplexicaulis on cancer cell lines MCF-7, WEHI-164 and normal cell line HUVEC.…”
Section: Discussionmentioning
confidence: 99%